2023
DOI: 10.1111/petr.14497
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and solid organ transplantation in adolescents and young adults: Current findings and implications

Abstract: Background Understanding the role of substance use is important in the equitable allocation of solid organs and may present an opportunity for improving outcomes among substance users who receive transplants. This scoping review presents findings related to substance use among pediatric and young adult transplant populations and suggests future directions. Methods A scoping review was conducted seeking studies related to substance use in pediatric and young adult transplant populations under the age of 39 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The burden of a serious health condition is an additional stress in this high-risk population. In a meta-analysis of substance use among pediatric and YA recipients of transplant, rates were similar to nontransplant peers and may lead to poorer outcomes 10 . In adults, pretransplant substance use is strongly associated with posttransplant nonadherence to substance use restrictions 11 and greater postoperative complications, increased risk for hospitalizations, and diminished QoL 12 .…”
Section: Barriers To Carementioning
confidence: 99%
See 1 more Smart Citation
“…The burden of a serious health condition is an additional stress in this high-risk population. In a meta-analysis of substance use among pediatric and YA recipients of transplant, rates were similar to nontransplant peers and may lead to poorer outcomes 10 . In adults, pretransplant substance use is strongly associated with posttransplant nonadherence to substance use restrictions 11 and greater postoperative complications, increased risk for hospitalizations, and diminished QoL 12 .…”
Section: Barriers To Carementioning
confidence: 99%
“…In a meta-analysis of substance use among pediatric and YA recipients of transplant, rates were similar to nontransplant peers and may lead to poorer outcomes. [10] In adults, pretransplant substance use is strongly associated with posttransplant nonadherence to substance use restrictions [11] and greater postoperative complications, increased risk for hospitalizations, and diminished QoL. [12] The need for a clear, directive policy regarding substance use, standard evaluation, and early intervention is supported by transplant providers.…”
Section: Substance Use and Substance Use Disordersmentioning
confidence: 99%
“…A recent review examined substance use among adolescents and young adults who were solid-organ transplant recipients or candidates [4]. The review found a total of 29 articles on substance use in this population with most being related to alcohol use and liver transplantation.…”
Section: Substance Use and The Transplant Populationmentioning
confidence: 99%
“…In general, substance use is believed to be similar or slightly below peer use, though there were no studies found on the use of cannabis or opiates in this population. There is some evidence that increasing substance use was associated with lower medication adherence though causality was limited by study methods [4]. Interestingly, the review noted one study [43] showing increased complexity of medication regimens was associated with lower alcohol use, with authors hypothesizing increased medication burden may lead to lifestyle changes and increased time management, which may limit youth from social outings where alcohol is present [4].…”
Section: Substance Use and The Transplant Populationmentioning
confidence: 99%
See 1 more Smart Citation